Temporal Dynamics of Diffusion Metrics in Early Multiple Sclerosis and Clinically Isolated Syndrome: A 2-Year Follow-Up Tract-Based Spatial Statistics Study - Schneider, Ruth; Genç, Erhan; Ahlborn, Christian; Gold, Ralf; Lukas, Carsten; Bellenberg, Barbara (Frontiers in Neurology, 2019)
Background: Tract-based spatial statistics (TBSS) is suitable for assessment of voxel-wise changes of fiber integrity in WM tracts, regardless of specific anatomic regions. Longitudinal TBSS analyses of early multiple sclerosis (MS) using 3 Tesla magnetic resonance imaging (MRI) are not common. Objective: To characterize microstructural WM alterations at initial diagnosis in clinically isolated syndrome (CIS) and early MS at baseline, and longitudinally over 2 years. Methods: DTI at 3Tesla was used to evaluate 106 therapy-naive patients with CIS or definite MS at baseline, and one (N=83) and two (N=43) year follow-up, compared to healthy controls (HC, N=49). TBSS was used for voxel-wise analyses of DTI indices for cross-sectional and longitudinal comparisons. Mean values of fractional anisotropy (FA), radial diffusivity (RD), and cluster voxel numbers were extracted from significant clusters using an atlas-based approach. Correlations with disability (EDSS) were calculated for FA and RD changes related to affected brain regions. Results: Reductions in FA were found at baseline in patients with CIS and RRMS compared to HC, and involved most supra- and infratentorial WM tracts. These changes negatively correlated with EDSS after 2 years in the cerebellum and cerebral peduncles. FA changes in patients with CIS and RRMS evolved in the second year, particularly in the descending projection pathways and the cerebellum, and were significantly associated with EDSS. RD alterations in patients compared to HC were undetectable at baseline, but were observed after 1 year and were exacerbated during the second year in all major supratentorial WM tracts, the corpus callosum, and the cerebellum. FA did not change between baseline and year one follow-up, but longitudinal investigation between the first and second year revealed combined dynamic FA and RD changes in the corpus callosum and corona radiata. Conclusion: TBSS of diffusion metrics at initial diagnosis and at two-year follow-up showed microstructural WM pathology and associations of FA reduction with future disability, respectively. Combined longitudinal FA and RD changes occurred in specific structures, where RD increases likely reflected Wallerian degeneration. The distinct temporal dynamics of FA and RD with constancy during the first year supports early therapeutic intervention for CIS and RRMS.